Impact of employment policies on disabled individuals in silvicultural activities - Ozel, Halil Baris; Sevik, Hakan; Cetin, Mehmet; Varol, Tugrul; Isik, Berkant (Springer Science and Business Media LLC, 2024)
AbstractThe prevalence of disability within societies necessitates empowering disabled individuals for their social and economic contributions. This study evaluates the impact of employment policies on the economy and well-being of disabled individuals in Turkey’s silvicultural sector during the COVID-19 pandemic. Focusing on physically disabled individuals engaged in silvicultural tasks from 2018 to 2021 in the Western Black Sea region it reveals an increase in their involvement despite a decrease in income, attributed to fewer workdays. The data collectively indicates that there was a minimum increase of 210% in the number of physically disabled individuals employed in silvicultural roles by private forestry companies between 2018 and 2021. The 3rd group, characterized by a 40–60% working capacity reduction, exhibited the highest employment rate, increasing from 56 individuals in 2018 to 137 in 2021. In contrast, the 2nd group (60–80% working capacity reduction) showed variable trends, reaching 11 employed individuals in 2020 before declining to 6 in 2021. Legal obligations often lead to employment in lowincome roles, hindering economic contributions. Male employment is higher, highlighting gender disparities. Education levels are generally low with recent increases in primary and secondary school graduates due to compulsory education. To create more inclusive opportunities disabled individuals could be trained for roles like planning and monitoring in forestry requiring specialized training.
Keywords: Employment; Silvicultural Works; Forestry; Disabled; 4. Education; 1. No poverty; 15. Life on land; 3. Good health; 8. Economic growth; 10. No inequality